Microplastic contamination and microbial colonization in coastal area of Busan City, Korea - Bae, Suyeon; Yoo, Keunje (Frontiers in Marine Science, 2022)
This study investigated the potential role of the concentration, shape, size, and polymer type of microplastics, in addition to the microbial community in six coastal areas of Busan city, South Korea. The results showed that the average MP concentration was 94 ± 41 particles·m-3, and particles sized 20–300 μm accounted for 67.5 ± 9.6% of the total MP abundance throughout the study sites. Further, polyethylene, polypropylene, and polystyrene polymers were abundant among the collected fragment- and fiber-shaped MPs, implying that highly populated and industrialized areas are major sources of MPs contamination. Moreover, the bacterial diversity and taxa-based on 16S rRNA gene was significantly different between MPs and seawater samples. Specifically, Psychrobacter, Pseudomonas, Flavobacterium, and Winogradskyella were significantly enriched in MPs compared with seawater (p <0.05). Redundancy analysis revealed that nutrient concentrations, salinity, and temperature potentially contributed to shaping the microbial communities on MPs. These results indicate the dynamic and complicated interactions of MP contamination with the physiochemical and environmental factors of the surrounding area. Our findings could provide that the understanding of MP contamination level and their characteristics as well as plastic bacterial colonization in urban coastal area.